The Gender Aspect of Immigrants' Assimilation in Europe - Taehoon Lee; Giovanni Peri; Martina Viarengo (Institute of Labor Economics (IZA), 2020)
The labor market performance of immigrants relative to natives has been widely studied but its gender dimension has been relatively neglected. Our paper aims at revisiting labor market convergence between immigrants and natives and examining this under-studied dimension in a comprehensive study of the EU-15 countries and Switzerland over the period 1999-2018. We measure convergence of labor market outcomes for male and female migrants to similar natives before and after the Great Recession and across countries of destination. Our results show that in most countries female migrants start with a larger employment gap but converge more rapidly than male migrants do. We also provide a broad overview of the role of potential factors such as economic conditions, labor markets structure, institutions and attitudes towards immigrants and women and their association with employment convergence of all immigrants and female immigrants specifically. While the analysis provides an interesting insight, we do not identify very significant factors at the national level. We find a very strong correlation between attitudes towards immigrants and their employment convergence across sub-national regions.
Keywords: J61; J00; J16; 330; international migration; labor market integration; gender gaps